Regression analysis of experimental data for added resistance in waves of arbitrary heading and development of a semi-empirical formula - Liu, Shukui (2021)
In this paper, we first conduct an extensive review of published experimental studies on the added resistance of a ship in waves to establish a common database. The data was enhanced by unpublished data from joint industry projects. Using this newly established database consisting of about 3,000 data points for 130 ships of different type and size, we develop an empirical formula for approximating the added resistance in regular waves of arbitrary heading. For the added resistance due to diffraction effect, we updated Faltinsen et al.'s (1980) asymptotic approach and introduced several semi-empirical parameters to approximate the added resistance in waves of various headings. The limited ship draft effect is examined analytically, while the hull form effects are taken into account empirically by regression of available data. For the radiation effect, the maximum value of added resistance and the corresponding wavelength for the various wave headings are determined by regression analysis of the experimental data. The developed formula is verified by application to typical ship types and sizes, both in the design and ballast conditions, at both design and low speeds. An error analysis for the various tested scenarios shows that the performance of the developed formula is satisfactory.